Jornada e parceria do casal no trabalho doméstico: um enfoque da psicologia analítica - Haddad, Julieta Maria Haical (2018)
This study aimed at exploring, from the discourse of couples, the way household chores are shared and at identifying agreements and disagreements between spouses and their attitudes toward the distribution of these chores at home. The instrument of this qualitative and exploratory research was a semi-structured interview based on a script specifically designed for the purpose of the study. Participants were five heterosexual couples, aging from 21 to 58 years old, with children and living in a city in the countryside of the State of São Paulo. Other inclusion criteria were that both spouses had a paid job and the aid of a housemaid once a week at most. The analysis of the interviews led to the establishment of categories which were articulated and interpreted based on the theoretical framework of the Analytical Psychology. The results indicate that the behavior of these couples no longer follows a traditional conception of gender roles, but rather it is structured around an agreement that implies a direct relation between paid and domestic work, the responsibility with the latter depending on the time invested on the former. The narratives suggest that this is a solution dictated by practical needs and does not eliminate conflicts, since it considers only one variable – time available for the accomplishment of house chores – not including the appreciation of individual preferences. No evidence has been found that this new arrangement is based on attitudes that take into account gender equality regarding rights and responsibilities. It is noteworthy that the fact of facing the burden of a double working day seems to contribute to both spouses associating negative emotions with domestic tasks, although there are more mentions of unpleasant emotions on the part of the wives, which implies that it would not be such a natural task for them and that perhaps the dissatisfaction comes from a culturally imposed sense of obligation that does not affect men. The research points to the conclusion that clinical psychologists may have their comprehension enriched by taking into consideration that couples, in their daily private routine – as seen in the study – do not realize the clash between their agreed choices and their unconscious conflicts or motivations